KAJIAN KINETIKA PENENTUAN LAJU REAKSI PENETAPAN KADAR VITAMIN C PADA BROKOLI (Brassica oleracea L) DENGAN METODE TITRASI TITRIMETRI - Ika Julianti Tambunan; Sulasmi Sulasmi; Siti Muliani Julianty (Journal of Pharmaceutical and Sciences, 2023)
Background: The damage to broccoli is caused by several factors, namely mechanical and biological. The value of freshness in broccoli can be seen from the rate of respiration, which will affect on weight loss, texture, moisture content, color changes, vitamin C content or increased physiological and microbiological activity. Methods of studying the kinetics of vitamin C oxidation reaction can be carried out through literature values, distribution turnover, distribution abuse tests, consumer complaints, and accelerated shelf-life testing. The objective of the research was to determine the effect of vitamin C levels on the reaction rate equation in terms of expired date. Objective: To determine the effect of vitamin C levels on the reaction rate equation in terms of the expiry date. Methods: This study uses a cross-sectional method, namely making observations by collecting data that has been going on and reviewing the results of research that has been going on. Results: showed that broccoli at room temperature storage had the highest vitamin C content, namely 7,216 mg, at 10C ± 2ºC broccoli contained vitamin C levels of 5.045 mg, at 5Cº ± 2ºC broccoli contained vitamin C levels of 4.283 mg and at temperature 0Cº ± 2ºC broccoli contains vitamin C levels of 4.713 mg. Conclusion: The conclusion of this study is that there is a relationship between vitamin C levels and the reaction rate equation in terms of expired date, from the results of the study it was found that there were changes in the reaction rate in the zero order, first order and second order based on storage temperature, the order that most affected the reaction rate equation was in zero order because the value of zero order r2 is close to 1